Postpartum Coccydynia: an Anatomy Overview - Reza Maulana; Nur Wahyuniati; Imai Indra (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Coccydynia is a term that refers to a painful condition in and around the coccyx. This symptom is typically a discomfort or pain which is felt when sitting for long time and when rising from sitting position. Many physiologic and psychological factors contribute to its etiology, but the majority of cases were found to be aggravated by pregnancy and childbirth (postpartum). Luxation and fracture of the coccyx are the two most common lesion of postpartum coccydynia. This poster shows an anatomy overview especially the coccyx to increase the understanding about this symptom